Systemic risk affected by country level development. The case of the European banking sector - Karkowska, Renata (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2019)
The goal of this study is to identify empirically how country level development affects the risk profiles of the EU banking sector. We examine the implications of banks’ activity and risk-taking that manifest themselves as spreading and growing instability. Additionally we explore the interaction between banking risk and structural, macroeconomic and financial market determinants. Through a dataset that covers 4678 European banks spanning the period 1996–2011 and the methodology of panel regression, the empirical findings document that credit, liquidity or insolvency risk are determined by market factors and could be systemic risk indicators in the banking sector. To show the heterogeneity of systemic risk determinants, the study sample was divided according to the economic development of a country into two groups: advanced and developing countries. The findings have implications for both bank risk management and regulators. This paper advances the agenda of making macroprudential policy operational
Argumenta Oeconomica, 2019, Nr 2 (43), s. 255-282
Keywords: banking; instability; systemic risk; credit risk; liquidity; bank solvency